IMPROVING STUDENT LEARNING MOTIVATION THROUGH GROUP GUIDANCE SERVICES USING THE RATIONAL EMOTIVE BEHAVIOR THERAPY (REBT) APPROACH - Delima Delima; Neviyarni Neviyarni; Netrawati Netrawati (Ensiklopedia of Journal, 2023)
Learning motivation is a factor that influences student achievement/students. The encouragement of motivational learning is a thing that needs to be raised in learning efforts at school. Rational Emotive Behavior Therapy (REBT) the approach to increase learning motivation is an effort to assist students/students to be able to optimize and develop the potential possessed by students/students. This study aimed to see the effectiveness of group counseling with the REBT approach to increase students' motivation to study. The Literature Review Study Method was used to search for articles in electronic databases, namely Google Scholar, Research Gate, and PubMed/Medline. Analysis conducted by the authors of the 8 relevant articles was obtained. Support and efforts are needed from the school to carry out group counseling services with the REBT approach to students as an effort to increase student motivation in learning.